Upaya Meningkatkan Kesejahteraan Siswa Melalui Konseling Komunitas Sekolah - Tita Tristiyani Eka Wardhani; Aep Kusnawan; Sugandi Miharja (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
School community counseling is a guidance and counseling approach that involves all elements of the school community—counselors, teachers, principals, parents, and the wider community—in providing psychological, social, and educational support for students. This approach is grounded in the school’s role as an environment for character development, prevention of negative behavior, and a space for cultivating students’ potential and overall well-being. This study discusses the concepts of counseling and community as defined by various experts, the fundamental principles of service delivery, the implementation of school community counseling, as well as the benefits and challenges that emerge in its practice. This research employs a literature study method to explore school community counseling by collecting and reviewing references from books and research journals. The findings indicate that school community counseling contributes to improving students’ social skills, learning motivation, emotional resilience, and the prevention of bullying. However, its implementation still faces obstacles such as limited resources, resistance to change, and insufficient collaboration among stakeholders. Therefore, stronger institutional support and policy reinforcement are needed to ensure that school community counseling can be implemented optimally and sustainably.